Impact of intracardiac echocardiography on readmission morbidity and mortality following atrial fibrillation ablation. (8th October 2022) - Deshpande, Saurabh; Sawatari, Hiroyuki; Ahmed, Raheel; Nair, Rakesh Gopinathan; Khan, Hassan; Khanji, Mohammed Y.; Somers, Virend K.; Chahal, C. Anwar A.; Padmanabhan, Deepak
Abstract: Introduction: The use of intracardiac echocardiography (ICE) is beneficial during the ablation of atrial fibrillation (AF). Evidence is conflicting regarding the clinical impact of using ICE on arrhythmia recurrence and mortality. Methods: Patients undergoing catheter ablation of AF during 2010–2017 were identified using the International Classification of Diseases‐9th and 10th Revision‐Clinical Modification (ICD‐9‐CM and ICD‐10‐CM) from the Nationwide Readmissions Database. Propensity matching was used to generate a control group. Patient demographics, Charlson comorbidity indexes, time from discharge to readmission, and the reason of readmission were extracted. Results: From 2010 to 2017, 51 129 patients were included in the analysis out of which ICE was used in 8005 (15.7%) patients. The in‐hospital mortality at readmission was significantly higher in the patients without ICE use (2.9% vs. 1.7%, p = .02). The length of stay (LOS) at readmission was significantly higher in non‐ICE arm (median [interquartile range, IQR]: 3 [2–6] vs. 2 [3–5] days, p < .0001) with similar healthcare‐associated cost (HAC) in both the groups (median [IQR]: US7507.3 [4057.8–15 474.2] vs. 7339.4 [4024.8–15 191.6], p = .43). Freedom from readmission was 12% higher (hazard ratio [HR] [95% confidence interval, CI]: 0.88 [0.83–0.94], p < .0001) with the use of ICE at 90‐day follow‐up, which was driven by 24% reduction in heart failure (HF) at follow‐up (HR [95% CI]: 0.76 [0.60–0.96], p = .02). Conclusions: ICE use during AF ablation procedure reduces readmissions at 90 days by 12%, driven by a 24% decrease in HF‐related admissions. The non‐ICE arm showed a significantly higher LOS which offsets marginally higher HAC in the ICE arm. Abstract :